Combating Antimicrobial Resistance Through Student-Driven Research and Environmental Surveillance - Fuhrmeister, Erica R.; Larson, Jennifer R.; Kleinschmit, Adam J.; Kirby, James E.; Pickering, Amy J.; Bascom-Slack, Carol A. (Frontiers in Microbiology, 2021)
Emerging resistance to all classes of antimicrobials is one of the defining crises of the 21st century. Many advances in modern medicine, such as routine surgeries, are predicated on sustaining patients with antimicrobials during a period when their immune systems alone cannot clear infection. The development of new antimicrobials has not kept pace with the antimicrobial resistance (AR) threat. AR bacteria have been documented in various environments, such as drinking and surface water, food, sewage, and soil, yet surveillance and sampling has largely been from infected patients. The prevalence and diversity of AR bacteria in the environment, and the risks they pose to humans are not well understood. There is consensus that environmental surveillance is an important first step in forecasting and targeting efforts to prevent spread and transmission of AR microbes. However, efforts to date have been limited. The Prevalence of Antibiotic Resistance in the Environment (PARE) is a classroom-based project that engages students around the globe in systematic environmental AR surveillance with the goal of identifying areas where prevalence is high. The format of PARE, designed as short classroom research modules, lowers common barriers for institutional participation in course-based research. PARE brings real-world microbiology into the classroom by educating students about the pressing public health issue of AR while empowering them to be partners in the solution. In turn, the PARE project provides impactful data to inform our understanding of spread of AR in the environment through global real-time surveillance.